Estimating the substitution elasticities of import of factory industries using micro data and comparing long-term and short-term elasticities. - Mehdi Yazdani; Mina Sadeghi (پژوهش‌های برنامه و توسعه)
Estimating the substitution elasticity of imported products is a key parameter for analyzing trade policies, especially trade integration issues. In general, this elasticity represents the intensity of the impact of import demand on domestic demand from the relative change in domestic price to import. In this study, the Armington substitution elasticity's were estimated for 103 industries four-digit ISIC in the period 1371-1396.The data used for domestic manufacturing production are extracted from the Statistical Center of Iran, the domestic and import price indices at the producer level from the Central Bank of Iran, and the trade data from the Islamic Republic of Iran Customs Administration.According to the results; the industries with the highest positive elasticities of substitution, respectively, are the "Manufacture of malt liquors and malt" and the "Manufacture of basic chemicals, except fertilizers and nitrogen Compounds" and Industries with the lowest positive substitution elasticity are, respectively "Tanning and dressing of leather" and "Building and repairing of pleasure and sporting boats except ships". Accordingly, in industries with positive substitution elasticity, it is possible to replace foreign consumption with domestically produced goods. Long-term elasticities are also significantly higher than short-term tensions (6.7 times).